ANALISIS SISTEM PENGUPAHAN BURUH HARIAN PABRIK PADI PADA PABRIK BERAS CV. DUA PUTRA HAURGEULIS, INDRAMAYU PERSPEKTIF FIQH MUAMALAH - Kurniawati, Kurniawati; Maulana, Rizal; Asrof Fitri, Ahmad (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
In Islam, human activities for life stages must be based on sharia principles. In sharia principles, one of the activities of renting services to get wages is known as ijarah. And as a Muslim in Indonesia, it is obligatory for us to carry out this ijarah in accordance with fiqh muamalah and laws and regulations. This study aims to explain the wage practices of rice factory workers that occur at the CV. Dua Putra Rice Factory and examine it based on the perspective of Fiqh Muamalah related to the implementation of the wage system for rice harvest workers at the CV. Dua Putra Rice Factory. This study applies a qualitative research method. This method is used so that the problems raised by researchers in this study can be answered comprehensively and represent the actual situation. While the type of research used is a case study where researchers conduct in-depth exploration of programs, events, processes, activities, towards one or more people. The data that has been collected is then analyzed using the Miles and Huberman model, which consists of data collection, data reduction, data presentation, and drawing conclusions or verification. The results of this study indicate first, that the wage system carried out by the CV Dua Putra rice factory uses a contract system with transaction details that are already known and agreed upon by both parties through an oral agreement. And second, the wage system carried out at the CV Dua Putra rice factory is in accordance with the ijarah contract, where the ijarah contract used is ijarah a'mal, which utilizes the labor of workers as the object of the contract and is in accordance with the principles of mubah, an-taradhin, justice, mutual benefit, and ta'awun but does not meet the written principles. Keywords: Wage system, daily laborers, rice factories, Fiqh Muamalah